Copyright infringement in printed materials: why it is happen / Syed Mohd Nazrin S. Hamzah and Reena Imbi - S. Hamzah, Syed Mohd Nazrin; Imbi, Reena (2015)
This is the report of the research entitled Copyright infringement in printed materials: why it is happen. The research consist of the findings that been obtained purely from the opinion and the response of the photocopy representatives and the student regarding the copyright infringement in printed materials. The copyright is one of the intellectual property in Malaysia. It is the method to protect the owner's work from being used to the public without any consent. As the copyright also being infringe nowadays, perceived as a crime, the infringement of the copyright in the printed materials, that is the photocopying behaviour seems to be ignored by the government. Due to such fact, this research paper will reveal and find out what is their response by the parties who involved in the printed materials, also finding the reason that lead to the copyright infringement in printed materials. This report consists of five (5) related compositions which are being presented in the form of chapters. The chapter 1 is the introduction; Chapter 2 includes the literature review and the analysis, Chapter 3 explaining the methodologies that have been applied. Chapter 4 is showing the findings and the analysis of the data. Chapter 5 briefing about the discussion and elaborates the research as the whole with the several list of suggestion and conclusion.